2009
DOI: 10.1128/ec.00363-08
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sorting of the Saccharomyces cerevisiae Vacuolar Protein Sna4p

Abstract: Sna4p, a vacuolar membrane protein, belongs to a small family of proteins conserved in plants and fungi. It is transported to the vacuolar membrane via the alkaline phosphatase (ALP) pathway, which bypasses the multivesicular bodies (MVBs). Here, we show that transfer of Sna4p by the ALP route involves the AP-3 adaptor protein complex, which binds to an acidic dileucine sorting signal in the cytoplasmic region of Sna4p. In addition, Sna4p can use the MVB pathway by using a PPPY motif, which is involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…We therefore monitored the behavior of GFP-tagged Sna2p and Sna4p. Previous studies in our laboratory that have focused on the targeting sequences of these proteins have shown that the addition of GFP or dsRed does not change the localization of the proteins (Pokrzywa et al, 2009;Renard et al, 2010). The results showed that, in addition to the known vacuolar localization of Sna2p and Sna4p, they are both concentrated in a 'vacuolar dot' (Fig.…”
Section: Pmp3p Binds To Phosphorylated Phosphoinositides Phosphatidisupporting
confidence: 54%
See 1 more Smart Citation
“…We therefore monitored the behavior of GFP-tagged Sna2p and Sna4p. Previous studies in our laboratory that have focused on the targeting sequences of these proteins have shown that the addition of GFP or dsRed does not change the localization of the proteins (Pokrzywa et al, 2009;Renard et al, 2010). The results showed that, in addition to the known vacuolar localization of Sna2p and Sna4p, they are both concentrated in a 'vacuolar dot' (Fig.…”
Section: Pmp3p Binds To Phosphorylated Phosphoinositides Phosphatidisupporting
confidence: 54%
“…Three homologs are present in yeast: Sna2p, Sna3p and Sna4p. Those three are respectively present at the vacuole membrane, lumen and both locations (Reggiori and Pelham, 2001;Stawiecka-Mirota et al, 2007;Pokrzywa et al, 2009;Renard et al, 2010). The SNA3 gene is in tandem with INO1, and the pattern of inositol-mediated regulation of the SNA3-INO1 tandem genes is similar (Shetty et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…This is reminiscent of the PMP3 family proteins in yeast with Pmp3p locating to the plasma membrane and Sna2p, Sna3p and Sna4p being delivered to the vacuole (Navarre and Goffeau 2000;Reggiori and Pelham 2001;Pokrzywa et al 2009). The failure of AtRCI2D to functionally complement the yeast pmp3 mutant (Medina et al 2007) might be explained if it was absent from the yeast plasma membrane in a similar manner to GFP-AtRCI2D in plant cells.…”
Section: Functional Specialization Of Rci2 Proteinsmentioning
confidence: 97%
“…A search of ScEno physical interactions in the Biogrid database identified APL6 as the only potential interacting protein with known functions in the vacuole [51, 52]. Apl6 is a beta3-like subunit of the yeast AP-3 complex that is involved in transporting proteins to the vacuole via an alternate pathway that bypasses multi-vesicular bodies [53-55]. Interestingly, APL6 interacts directly or indirectly with the six yeast proteins that are missing from vacuoles in enolase-deficient yeast, at least one of which, Vam3, is known to be transported to the vacuolar membrane by this alternate pathway [56].…”
Section: Discussionmentioning
confidence: 99%